The process of treatment and care of a child with neurofibromatosis type 1 requiring nutritional treatment – case report - Kram, Mirosława; Barczykowska, Ewa; Kurylak, Andrzej; Pałgan, Izabela (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Introduction: The nutritional treatment is to ensure the patient an adequate supply of nutrients, mineral salts and vitamins, whenever it is not possible or there are restrictions in the supplying food by oral intake. In pediatric such a method of treatment of seriously ill children is well recognized starting from the 80s of last century. Purpose: The purpose of this study was to analyze the process of treatment and care of the child suffering from neurofibromatosis type 1 (NF-1) requiring nutritional treatment. Material and methods: The paper describes the course of treatment and care of the child with severe NF-1 based on analysis of medical and nursing documentation. The research was deepened by the interview/conversation with the mother, and clinical observations. The study was approved by the Bioethics Committee No 369/2010. Results : In addition to the skin lesions of type café au lait (“coffee with milk”) and many nodules (neurofibromas), the patient has a brain tumor – glioma of the optic nerve. Progression of changes in the central nervous system resulted in tetraparesis, regression of psychomotor development and cachexia. The child was treated with nutritional treatment, oncological chemotherapy, and was treated according to nursing process. The patient was qualified for palliative care. Conclusions : A child with NF-1 requires interdisciplinary hospital and ambulatory care. 2. Parents need continuous information, as well as emotional and spiritual support.